Lifestyle interventions in the maritime settings: a systematic review - Fereshteh Baygi; Shirin Djalalinia; Mostafa Qorbani; Masoumeh Dejman; Jesper Bo Nielsen (Komiyama Printing Co. Ltd, 2020)
Abstract Background Evidence on workplace health promotion interventions at sea is scattered and includes different methodological approaches. The continued focus on lifestyle and health promotion on land-based industries makes it pertinent to evaluate available data from maritime settings to gain systematic knowledge on the field. Methods In this systematic review, we systematically searched PubMed and NLM Gateway (for MEDLINE), Institute of Scientific Information/Web of Science (ISI/WOS), and SCOPUS up to January 2019 using standard keywords including lifestyle interventions in the maritime setting. Two independent reviewers assessed papers and extracted the data. The quality of included studies was assessed using the Cochrane Risk of Bias tool. Due to significant heterogeneity between studies, the effectiveness of interventions was presented as a qualitative synthesis. Results After the initial search and refinement based on a total of 4432 records, ten articles met eligibility criteria and were included in the final review. Six studies originated from US maritime settings, 3 studies were conducted on Danish seafarers and one study came from Finland. The main focus of 6 studies was educational interventions including stress management, healthy eating, anti-smoking and anti-drinking sessions, sexual behavior program, and advice about preventive strategies. Four studies described the implementation of interventions, including micro-nutrient supplementation, physical activity, and pharmacotherapy. Follow-up assessments occurred over a time period ranging from 80 days to 2 years. Three studies found a positive though limited effect of structural and/or education interventions in maritime settings. The quality of all included studies was modest. Conclusion Results of this systematic review show that a limited number of studies of lifestyle interventions in the maritime setting exist and that the quality of them is generally modest. Also, most of the interventions identified have failed to demonstrate substantial health benefits for seafarers. Systematic review registration number in PROSPERO: CRD42019134533